Grafting modification for textile functionalization: innovations and applications - Joyjit Ghosh; Nishat Sarmin Rupanty; Faizunnesa Khan; Tasneem Noor; Rifat Jahangir; Seyedali Mirmohammadsadeghi; Tarikul Islam (Discover Applied Sciences)
Abstract The functionalization of textiles through grafting modification has emerged as a promising approach, offering a bright future for the textile industry. This process involves the covalent attachment of functional polymers to textile substrates, imparting desirable properties such as hydrophobicity, antimicrobial activity, UV resistance, drug delivery capabilities, flame resistance, and improved dyeability. Various grafting techniques, including chemical, plasma-induced, and radiation-induced grafting, have been explored to achieve these modifications. This review highlights advancements in grafting methods, selecting suitable grafting agents, and the resulting functional properties conferred on textiles. The discussion also addresses the environmental and economic aspects of grafting modification, emphasizing sustainable practices and applications. The integration of grafting modification into textile manufacturing processes offers significant opportunities for developing high-performance textiles with tailored functionalities, meeting the evolving demands of consumers and industries. This constant evolution and adaptation to meet these demands keeps our industry vibrant and engaging.